Trade-off analysis between machining time and energy consumption in impeller NC machining. (February 2017) - Arriaza, Oscar Velásquez; Kim, Dong-Won; Lee, Dong Yoon; Suhaimi, Mohd. Azlan
Abstract: Electrical energy is directly linked to society's prosperity across the globe; much of this due to the diverse innovations on manufacturing processes. Keeping pace with the high energy demand growth will require constant efforts in terms of investment and research in order to bring new alternatives of usage. This paper outlines the application of multiple response optimization in order to analyze the trade-off between machining time and energy consumption in 5-axis impeller rough machining to find a possible balance between them. It is well known that a higher speed reduces machining time but increases energy consumption, and vice versa. A quantitative form of the relationship between the involved factors was obtained by utilizing response surface methodology (RSM) together with the desirability function method. Four independent factors were selected, namely, spindle speed, feed rate, depth and width of cut. The responses are the consumed energy and the machining time. The results showed that selecting an appropriate feed rate is crucial to balance the trade-offs between energy and time. Spindle speed is the major factor for energy consumption, while width of cut is the most influential factor for machining time. Highlights: Multiple response optimization of the cutting conditions for impeller roughing. Substantial improvement by balancing the factors in machining processes. Balancing factors can be the best optimization for a multiple response problem. 2.7mm of width, 1.8mm of depth, 8, 000 rpm, and feed 740 mm/minprovide best balance. The proposed model showed congruence between theoretical and practical results.